2018
DOI: 10.1177/0886260518759058
|View full text |Cite
|
Sign up to set email alerts
|

Child Victimization and Polyvictimization Among Young Adults in Northern Chile

Abstract: This study examined the prevalence of victimization and polyvictimization and gender differences in young adults from Arica in northern Chile. In all, 718 college students participated (46.9% men, 53.1% women), aged between 17 and 28 years old ( M = 21.6; SD = 4.11). The Spanish version of Juvenile Victimization Questionnaire ( JVQ) was used to access five categories of child victimization (conventional crime, child maltreatment, peer and siblings victimization, sexual victimization, and indirect victimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
0
3
0
5
Order By: Relevance
“…Another element that may influence the reliability levels is the low number of items. Eventually, other indicators could be considered to evaluate the reliability of the JVQ with different and more robust results [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Another element that may influence the reliability levels is the low number of items. Eventually, other indicators could be considered to evaluate the reliability of the JVQ with different and more robust results [ 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…Del mismo modo, las autoras determinaron que el método de víctimas por encima de la media y el 10% superior más victimizado tenían el menor grado de consistencia. Sin embargo, estos dos métodos han sido aplicados simultáneamente en una gran cantidad de estudios (Bogolyubova et al, 2015;Pereda et al, 2017;Pereda, Abad y Guilera, 2015;Pereda et al, 2014;Pinto-Cortez et al, 2018;Pinto-Cortez et al, 2017;Segura et al, 2015).…”
Section: Estudios Que Utilizan El 10% Superior Más Victimizado Con Los Puntos De Corte Y Las Prevalencias En Los Dos Marcos Temporalesunclassified
“…Otros estudios (Bogolyubova et al, 2018;Guerra et al, 2017;Pinto-Cortez et al, 2018) utilizan la versión retrospectiva para adultos. El JVQ está diseñado para detectar la victimización sufrida en un periodo de tiempo relativamente corto, y aunque esta versión permita identificar la victimización completa durante la infancia y la adolescencia, se debe tener precaución puesto que algunos tipos específicos de victimización pueden ser difíciles de recordar con el paso del tiempo .…”
Section: Versión Del Cuestionario De Victimización Juvenilunclassified
See 1 more Smart Citation
“…Experiencing situations of violence during important stages of physical and psychological development can compromise psychological adaptation over time [11]. Thus, the international literature that was more focused on developmental victimology has shown that some children and adolescents may experience more than one type of violence throughout their lives [12][13][14], and that these incidents are sometimes interconnected, even if apparently different [15], creating a cumulative risk [16]. Studies in the field of juvenile victimology, and the consideration of the co-occurrence and implications of these for the development of children and adolescents, are important to allow a better understanding of phenomena such as multiple victimization or polyvictimization, and the development of intervention practices that are appropriate for the problem [17,18].…”
Section: Introductionmentioning
confidence: 99%